Science studies during the Cold War and beyond : paradigms defected - Aronova, Elena, 1965- 1965- Herausgeber; Turchetti, Simone Herausgeber; Alfried Krupp Wissenschaftskolleg Greifswald; International Conference "Politics and Context of Science Studies During the Cold War and Beyond" (2012, Greifswald) (Palgrave studies in the history of science and technology, 2016)
This book recounts how during the Cold War the study of science moved to the centre of academic through the creation of the new discipline of science studies. In this way the volume charts the importance of these studies for the trajectory of Cold War nations through the elaboration of new national science policies and the transnational dialogue, even across the Iron Curtain, between key scholars involved in shaping their trajectory. By examining how a new group of intellectuals was mobilized by state administrators to convincingly set up a discipline deemed to have major repercussions on the advancement of science in developed and undeveloped nations. Secondly, by putting the study of science at the centre of the dialogue (as well as the confrontation) between nations and Cold War blocs. The volume thus shows how an often considered arcane field of enquiring had in fact major implications for the understanding and fostering of Cold War science